Intraseasonal variability of the genesis potential index and its relationship with tropical cyclogenesis over the western North Pacific. (30th June 2019) - Zhang, Wei; Gao, Jianyun; Cheung, Kevin K. W.; Chen, Jau‐Ming; You, Lijun
Abstract: The intraseasonal variability (ISV) of the genesis potential index (GPI) and its relationship with tropical cyclone (TC) genesis over the western North Pacific (WNP) are examined for the summer (May–October) during 1982–2016. The distribution of GPI is separated into three sub‐regions as South China Sea (SCS), western part of WNP (WWNP) and eastern part of WNP (EWNP). All three regions have a statistically significant power spectrum peak in the 10–20‐day period, associated with 20–30‐ and 50–70‐day signals in SCS and 20–30‐day signal in WWNP. The ISV of GPI in the SCS is the most intense among these three regions, whereas the weakest one is in the EWNP. On average, ISVs of GPI (including 10–20‐day, 20–30‐day and 30–70‐day components) account for about 28% of the total variance of GPI. About 83% of TCs form when at least one ISV component is in its wet phase. We further examine the spatial patterns of GPI intraseasonal oscillation (ISO) through empirical orthogonal function (EOF) analysis performed on the 10–90‐day filtered GPI data. There are 61% of TC formations in the first three spatial modes during the typical phases with anomalous PC. The ISV of GPI can indicate the TC sub‐seasonal genesis on both frequency and location. Regression analysis on different time‐scales, which is based on either the three sub‐regions or statistical spatial modes, is able to conclude that oscillations of GPI are associated with ISO signals from different regions: 10–20‐day from WNP; 30–70‐day from Indian Ocean; 20–30‐day from both WNP and Indian Ocean. In the boreal summer, the northward propagation of ISO accompanied with anomalous convection and circulation influences GPI ISO in the WNP, which can be a good indicator for TCs genesis. Such relationship can be applied to develop extended‐range forecasting of tropical cyclogenesis. Abstract : The intraseasonal variability (ISV) of the genesis potential index (GPI) and its relationship with tropical cyclone (TC) genesis over the western North Pacific (WNP) are examined for the summer (May‐October) during 1982 to 2016. The ISV of GPI can modulate the TC subseasonal genesis on both frequency and location. In the boreal summer, the northward propagation of ISO accompanied with anomalous convection and circulation influences GPI intraseasonal oscillation in the WNP, which in turn modulates the TC genesis frequency and location. It should be noticed that we have assigned opposite sign to the spatial mode of EOF1 and PC1 at the same time to make sure that the TCs genesis locations have positive GPI.